Understanding Sibling Correlations in Education: Molecular Genetics and Family Background - Jason M. Fletcher; Qiongshi Lu; Bhashkar Mazumder; Jie Song (Institute of Labor Economics (IZA), 2023)
Sibling correlations in socioeconomic status are one of the key measures of equality of opportunity and social mobility, providing an omnibus examination of the importance of family background. Typically, these correlations are interpreted as the combined effects of shared sibling background and experiences, including genetics and family environments. The UK Biobank allows us to specifically control for sibling and parental genetics (polygenic scores, PGS) in order to gauge their relative importance compared with broader family background effects. We use >17,000 sibling pairs from the UK Biobank in order to further decompose standard sibling correlations of educational attainment found in the literature. In general, we find modest (up to 20%) contributions of molecular genetics to the similarity of sibling outcomes, suggesting a large amount of the observed similarity in sibling educational outcomes are due to parents and environments of children.
Keywords: J62; J12; J24; 330; sibling correlations; educational mobility; genetics